2016
DOI: 10.1021/acs.joc.5b02756
|View full text |Cite
|
Sign up to set email alerts
|

Selective Prenylation of Protected Phenols for Synthesis of Pawhuskin A Analogues

Abstract: Pawhuskin A is a prenylated stilbene that functions as an antagonist of the kappa opioid receptor. Analogues of this natural product bearing different placements of the prenyl group in the A-ring have shown selectivity for either the kappa or the delta receptors subtypes. This differential activity has drawn attention to regiospecific preparation of the C-2, C-5, and C-6 prenylated A-ring regioisomers. Through halogen metal exchange, advanced intermediates representing each of these regioisomers have been prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…By treatment of bromide 54 under similar halogen metal exchange conditions, but in THF instead of Et 2 O, the ratio of the two products approximately reversed and the alkylated compound 55 was the major product. 42 A similar and equally dramatic solvent effect has been reported by Bridges and coworkers. 51 NaH, CH 3 Figure 16.…”
Section: Chapter 2 Selective Synthesis Of A-ring Isomers For Analoguesupporting
confidence: 74%
See 3 more Smart Citations
“…By treatment of bromide 54 under similar halogen metal exchange conditions, but in THF instead of Et 2 O, the ratio of the two products approximately reversed and the alkylated compound 55 was the major product. 42 A similar and equally dramatic solvent effect has been reported by Bridges and coworkers. 51 NaH, CH 3 Figure 16.…”
Section: Chapter 2 Selective Synthesis Of A-ring Isomers For Analoguesupporting
confidence: 74%
“…By changing the base from NaH to LiHMDS, it was clear by 31 P NMR that the major product again was alkylation at the carbon alpha to the phosphonate. 42 Although prenylation at the alpha carbon originally was not desired, when it became important a more efficient synthetic route towards this prenyl compound was developed. This approach could be based upon treatment of phosphonate 35 with only one equivalent of LiHMDS and it was found that these more simplistic conditions could provide the prenyl compound 36 in great yield.…”
Section: Chapter 2 Selective Synthesis Of A-ring Isomers For Analoguementioning
confidence: 99%
See 2 more Smart Citations
“…The MOM ester 19 proved to be sufficiently stable to allow halogen-metal exchange and alkylation with geranyl bromide to give the ester 20 in moderate yield. 24 …”
Section: Resultsmentioning
confidence: 99%